Les violences politiques dans les Etats de la Caraïbe insulaire (1945 à nos jours) - Laurent Jalabert (Amnis)
Political violence has been a constant in the political life of the independent states of the Caribbean Islands (Cuba, Haiti, Santo Domingo, Jamaica, Trinidad and Tobago…) from 1945 to the present times. Political violence has developed into a form of political culture, in authoritarian regimes (Cuba, Haiti, Santo Domingo), as well as in countries engaged in a democractic process (Haiti, Santo Domingo) or even in the democracies (Jamaica, Trinidad and Tobago). A comparative approach reveals obvious differences in the degree of violence, according to the nature of the regimes, and the nuances in each type. In spite of these varying degrees, which can extend to systematic use of terror, political violence is nonetheless common practice in all these countries as a ruling method for the government and a means of expression for the civilian society. Violence is undoubtedly a form of the political culture of the Caribbean Island’s states.